Tlatelolco platform on environment and development (UN.ECLAC, 2011)
In adopting this Platform LAM and Caribbean countries agreed on principles and initiatives to help ensure sustainability of the development processes in the region. They identified critical areas such as finance, natural resources protection and poverty..
Keywords: SUSTAINABLE DEVELOPMENT; ECONOMIC DEVELOPMENT; ENVIRONMENTAL PROTECTION; TECHNOLOGY TRANSFER; POVERTY; LATIN AMERICA; CARIBBEAN